Altai and Tuva: the beauty and the savage - Tarbastaeva, Inna S. (The New Research of Tuva, 2014)
The author cogitates over the scientific expedition to the Republic of Altai about the differences in mentalities and behavior of Altai people and Tuvans.
Keywords: Altai people; Republic of Altai; Tuva; Tuvans